MODIFIKASI PERILAKU UNTUK MENINGKATKAN KETERAMPILAM SOSIAL ANAK - MUTIAH, DIANA (Program Studi Magister Pendidikan Anak Usia Dini, 2016)
Abstract: The aim of the research to the development of model behaviour modification in improvement of children’s social skills. Research and development of Social Skills Model through Behaviour Modification Technique are based on three concept theory: Albert Bandura’s Social Cognitive Theory, Martin and Pear’s Behavior Modification and Cartlege’s the concept of Social Skills. Learning is classified into three domains namely cognitive, affective and psychomotor, in accordance with Bloom’s Taxonomy. The improvement of social skill reflected from non-adaptive behavior. This behavior can be carefully observed by classroom teacher. Based on data from instrument, interviews and observations, categorization of behaviors and its measurement can be carried out through the data pre and post test. The development of social skills are encouraged by behavior modification techniques such as modeling, reinforcement, punishment, prompt, relaxation, shaping. Research suggests that cognition and learning contract that involves process of thinking through discussion among students in the classroom are needed. Keyword : Research and Development, Social Cognitive, Behavior Modification, Social Skills Abstrak. Penelitian ini bertujuan untuk mengembangkan model modifikasi Perilaku dalam rangka meningkatkan keterampilan sosial anak. Model dikembangkan dari tiga konsep teori. Pertama, Teori Sosial Kognitif dari Albert Bandura. Kedua, Teori Modifikasi Perilaku dari Martin dan Pear. Ketiga, Konsep Keterampilan Sosial dari Cartlege dan Milburn. Pelaksanaan pembelajaran mengembangkan tiga ranah sesuai dengan Taksonomi Bloom, yaitu ranah kognitif, afektif dan psikomotorik. Perkembangan keterampilan sosial dengan menggunakan tehnik modifikasi perilaku yaitu modelling, penguatan (reinforcement), token economy, punishment, prompt, relaksasi, dan shaping. Berdasarkan hasil penelitian ditemukan perlunya kesadaran kognisi dan kontrak belajar yang melibatkan proses berfikir siswa melalui diskusi bersama di kelas. Kata kunci: Penelitian dan Pengembangan (R&D), Sosial Kognitif, Modifikasi Perilaku dan Keterampilan Sosial.